Identification of a novel m5C/m6A-related gene signature for predicting prognosis and immunotherapy efficacy in lung adenocarcinoma - Ma, Yiming; Yang, Jun; Ji, Tiantai; Wen, Fengyun (Frontiers in Genetics, 2022)
prognosisPurpose: Lung adenocarcinoma (LUAD) is the most prevalent subtype of non-small cell lung cancer (NSCLC), leading to high mortality. However, there is still lacking in effective methods to guide clinical therapeutic strategies for LUAD. This study aimed to analyze the relationships between a m5C/m6A-related signature and LUAD, and construct a novel model for evaluating prognosis and predicting drug resistance and immunotherapy efficacy. Methods: We obtained data of LUAD patients from TCGA and GEO datasets. According to differently expressed m5C/m6A-related genes, we identified distinct m5C/m6A-related modification subtypes in LUAD by unsupervised clustering and compared differences of functions and pathways between different clusters. In addition, a risk model was constructed by multivariate Cox analysis based on prognostic m5C/m6A-related genes to predict prognosis and immunotherapy responses. Results：We showed the landscape of 36 m5C/m6A regulators in TCGA LUAD samples and identified 29 differently expressed m5C/m6A regulators between normal and LUAD groups. Two m5C/m6A-related subtypes were identified with the 29 genes. Compared with Cluster2, Cluster1 had lower of m5C/m6A regulator expression, higher OS, higher immune activity and abundance of infiltrating immune cells. A four m5C/m6A-related gene signature consisting of HNRNPA2B1, IGF2BP2, NSUN4 and ALYREF was used to construct prognostic risk model, and high-risk group had worse prognosis, higher immune checkpoint expression and tumor mutational burden (TMB). In patients treated with immunotherapy, samples with high risk scores had higher expression of immune checkpoint genes and better immunotherapeutic efficacy than those with low risk scores. Conclusions: We conclude that the m5C/m6A regulators related risk model could serve as an effective prognostic biomarker and predict therapeutic sensitivity of chemotherapy and immunotherapy.